Photosynthetic pigments, nitrogen status, and flower behavior in eggplant exposed to different sources and levels of potassium - Marques, Douglas José; Broetto, Fernando [UNESP]; Lobato, Allan Klynger da Silva; Silva, Ernani Clarete da; Carvalho, Janice Guedes de; Ávila, Fabrício William de; Alves, Gustavo Antonio Ruffeil; Andrade, Izabelle Pereira (My University, 2012)
The aim of this study was to investigate (i) the influence of different sources and levels of potassium on photosynthetic pigments, (ii) measure nitrogen status in leaf, (iii) evaluate flower behavior in eggplant (Solanum melongena L.), and (iv) to identify a better potassium source to cultivation of this species. The experiment design used was in factorial scheme with randomized blocks, being composed by 2 potassium sources (KCl and K2SO4), combined with 4 levels of K2O (250, 500, 750 and 1000 kg ha-1). Nitrogen accumulation in leaf at 50 days after transplanting had a higher value with KCl compared with K2SO4. Results linked to aborted fruits presented similar effects to KCl and K2SO4. This study revealed that eggplant exposed to excess potassium did not have a negative effect on chlorophyll a and b, and nitrogen concentration in leaf was significantly modified due to increase in potassium level. In addition, greater levels of potassium produced negative consequences linked to flower and fruit abortion. Therefore, potassium source indicated for eggplant is potassium sulfate.
Keywords: Solanum melongena L.; Potassium; Flower; Pigments; Nutrition plant